TI_GERICHTE 12.2017.161 vom 10. April 2019 , Blocco cautelare del RC - fallimento della società convenuta - interesse degno di protezione - TI Tribunale d'appello (2019)
Blocco cautelare del RC - fallimento della società convenuta - interesse degno di protezione